Anti-toxicogenic fungi and toxin-reducing effects of bacillomycin D in combination with fungicides. (September 2022) - Sun, Jing; Zhou, Yan; Liu, Huawei; Ni, Jindong; Lu, Fengxia; Bie, Xiaomei; Lu, Zhaoxin; Lu, Yingjian
Abstract: Mycotoxins are toxic secondary metabolites produced by fungus including Aspergillus and Fusarium . They can contaminate food and cause major health issues. Bacillomycin D (BD) is a natural antimicrobial lipopeptide generated by Bacillus that has excellent antifungal capabilities, but its high price prevents it from being widely used. Chemically produced and essential oil-based fungicides are also currently the most frequent types. In the study, the effects of combining BD with two types of fungicides on the growth of toxicogenic fungi as well as the generation of deoxynivalenol (DON) and fumonisin B1 (FB1 ) were examined. It was discovered that BD was more effective in suppressing molds than the other two types of fungicides, and it could be combined with synthetic or essential oil-based fungicides to provide a synergistic or additive effect. BD 31.25 μg/mL + Thymol (Thy) 7.81 μg/mL and BD 11.45 μg/mL + Cinnamon oil (Cin) 3.90 μg/mL inhibited F. graminearum, respectively. The combination of BD+Thy and BD+Cin at this concentration considerably reduced 60%–80% spore germination, when DON dropped below 300 ng/L. Furthermore, both combinations suppressed F. moniliforme growth and FB1 synthesis in a dose-dependent manner at lower concentrations. At an action dose of 2 MIC, FB1 production might be reduced to less than 100 ng/L. Our findings indicated that BD might interact synergistically with various fungicides, suggesting that it could be useful in the field of antifungal and toxicity reduction in food. Graphical abstract: Image 1 Highlights: Bacillomycin D (BD) has a good fungicidal effect, with an MIC below 62.5 μg/mL. BD and fungicides could be synergistic or additive to reduce the amount of fungicide used. BD with thymol or cinnamon oil significantly inhibited fungi growth and mycotoxins production.